1998
DOI: 10.1046/j.1468-2982.1998.1806313.x
|View full text |Cite
|
Sign up to set email alerts
|

Photophobia and Phonophobia in Tension-Type and Cervicogenic Headache

Abstract: Light and sound-induced discomfort and pain thresholds were measured in 26 patients with cervicogenic headache, in 40 patients with tension-type headache, and in 100 headache-free controls. Neither headache group was significantly different as to photophobia and phonophobia, but both were significantly more sensitive to light and sound than controls (p<0.0001), even when patients were tested in the headache-free period (p<0.05). Episodic and chronic tension-type headache had similar photo- and phonophobia thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…We add that these sensitivities, if elevated during TTH, do not dissipate in the absence of headache, and that this holds true for tender and nontender points. These findings are consistent with a recent study demonstrating increased photo-and phonophobia in TTH patients both in and out of headache episodes (15). We also demonstrate that the geographic stability of the most-tender point can be unstable.…”
Section: Discussionsupporting
confidence: 93%
“…We add that these sensitivities, if elevated during TTH, do not dissipate in the absence of headache, and that this holds true for tender and nontender points. These findings are consistent with a recent study demonstrating increased photo-and phonophobia in TTH patients both in and out of headache episodes (15). We also demonstrate that the geographic stability of the most-tender point can be unstable.…”
Section: Discussionsupporting
confidence: 93%
“…Most studies that have looked at thresholds of light in individuals showed some normal variation (27). However, subjects with migraine and even tension-type and cervicogenic headache (27) have lower thresholds (27, 99). Light sensitivity may also vary by season.…”
Section: Anatomy and Pathophysiology Of Photophobiamentioning
confidence: 99%
“…Although both headache groups were more sensitive to light and sound compared to controls even in the headache-free periods, no differences were found in patients with CEH when tested with and without pain. It is striking, however, that patients with CEH showed a greater photophobia on the symptomatic than on the nonsymptomatic side, whereas no such differences were found in TTH and other unilateral headaches [12].…”
Section: Introductionmentioning
confidence: 80%
“…In a recent study by Vingen and Stovner [12], light and sound-induced discomfort and pain thresholds have been measured in patients with TTH, CEH, and in headache-free controls. Although both headache groups were more sensitive to light and sound compared to controls even in the headache-free periods, no differences were found in patients with CEH when tested with and without pain.…”
Section: Introductionmentioning
confidence: 99%